1996
DOI: 10.1523/jneurosci.16-23-07428.1996
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Protein Synthesis Inhibition on the Activity-Dependent Expression of BDNF Transcripts: Evidence for Immediate-Early Gene Responses from Specific Promoters

Abstract: In the adult rat forebrain, brain-derived neurotrophic factor (BDNF) expression is very rapidly induced by neuronal activity, suggesting that this might occur without intervening protein synthesis. The rat BDNF gene has four differentially regulated promoter regions; each gives rise to an mRNA containing a unique 5' exon (I-IV) and a common 3' exon (V) that codes for mature BDNF protein. The present study used exon-specific in situ hybridization and both in vivo and in vitro preparations to determine whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(82 citation statements)
references
References 52 publications
4
78
0
Order By: Relevance
“…Among the major BDNF isoforms expressed in the brain and investigated in this study, we found that exons IV and VI are regulated by acute stress, although their responsiveness is differently affected by chronic antidepressant treatment. The rapid modulation of exons IV and VI is in agreement with the possibility that they might be induced as 'immediate early genes,' without intervening protein synthesis (Lauterborn et al, 1996). Levels of exon IV mRNA were significantly upregulated by stress independently from DLX administration, although the magnitude of this effect is larger in antidepressant-treated rats.…”
Section: Stress-dependent Bdnf Modulation After Duloxetine R Molteni supporting
confidence: 80%
“…Among the major BDNF isoforms expressed in the brain and investigated in this study, we found that exons IV and VI are regulated by acute stress, although their responsiveness is differently affected by chronic antidepressant treatment. The rapid modulation of exons IV and VI is in agreement with the possibility that they might be induced as 'immediate early genes,' without intervening protein synthesis (Lauterborn et al, 1996). Levels of exon IV mRNA were significantly upregulated by stress independently from DLX administration, although the magnitude of this effect is larger in antidepressant-treated rats.…”
Section: Stress-dependent Bdnf Modulation After Duloxetine R Molteni supporting
confidence: 80%
“…Significant increases in exon II expression were also evident following antidepressant/exercise combinations for 7 or 14 days. Consistent with an immediate early gene mode of expression (Lauterborn et al, 1996), hippocampal levels of the exon III variant were enhanced following shortterm treatment only; no changes were evident following chronic treatment (14 days). It should be noted that shortterm exercise/antidepressant combinations (using both reboxetine and citalopram) were particularly effective in elevating the expression of exon III (Figures 1d, 2d and 3d).…”
Section: Discussionmentioning
confidence: 64%
“…The TIMP-1 gene also shares with c-fos (Morgan and Curran, 1991) and BDNF (Hughes et al, 1993;Lauterborn et al, 1996) the property of being transcribed as an IEG. Indeed, cycloheximide did not block the KA-mediated induction of TIMP-1 mRNA but did block the induction of Fos protein, indicating that protein synthesis was successfully inhibited, as previously demonstrated in vivo (Jonec and Wasterlain, 1979;Goto et al, 1990;Papas et al, 1992).…”
Section: The Early Timp-1 Mrna Induction In Neurons Is Independent Ofmentioning
confidence: 99%